No ritmo do Passinho: deslocamentos midiáticos e estetização cotidiana do grupo Dream Team do Passinho - Menezes, Darciele Paula Marques (2017)
The present study aims to understand the media movements and the negotiations carried out by the Dream Team group of Passinho - main representation of the cultural identity movement Passinho - to maintain the visibility acquired. For this, it was established as a problem question: how Passinho's Dream Team, originated from a cultural-identity movement called the Passinho, constitutes and maintains its visibility before the facilitation of the production processes, the new channels of circulation and dissemination in the sphere mediatic? In order to answer this question, the general objective is to investigate the strategic articulations presented by Passinho's Dream Team, which culminate in the re-signification of social discourses and processes of daily aesthetization. The specific objectives were: (1) to map how the insertion of the Passinho's Dream Team in digital media and its respective presence in the mass media takes place; (2) compare DTP Passinho's discourse in digital media, with discourses constructed by and / or in the mass media; (3) to analyze when the partnership of renowned companies the DTP group occurs and the influence on the discourse presented by the same, redirected it to consumption; and (4) demarcate the performance of the Passinho's Dream Team and its negotiation actions to maintain the visibility achieved. In order to answer the questions posed in this thesis, the socio-demographic support (LANDOWSKI, 1992), combined with data obtained through free digital data analysis software, specifically Gephi and Netlytic, is used as a theoretical and methodological support. generate intelligible ways to view a large volume of data. It was also used the non-participant covert observation, in which the researcher does not participate in the investigated group, so the observed ones do not know that they are being studied (JOHNSON, 2010). Thus, in view of the analysis made, it was possible to understand that Passinho's Dream Team has an indisputable ability to create networks, since in addition to establishing certain relationships with social and media actors, they use these relationships at different times, the collaboration of these actors in strategic moments. In addition, the group builds and maintains its digital social networks as places of intense self-expression, in which fragments of television appearances are recovered, they use an informal language in order to get closer to the daily life lived in the slums of the Rio de Janeiro favelas, demarcate your identity. The self-referentiality corresponds to the main strategy maintained by the group through the initial media displacements and subsequent discursive displacements between digital media Facebook, YouTube, Instagram and Twitter.